Implementation of Tsukamoto Fuzzy Logic in IoT Based Dam Water Level Measuring System Using Nodemcu ESP8266 - Sofyan Sofyan; Siti Nur Asia; Muh Imam Quraisy; Irfan Irfan (Jurnal JEETech, 2026)
The measurement of dam water level is an important aspect in water resource management and flood risk mitigation. Conventional monitoring systems still have limitations in terms of accuracy, efficiency, and the availability of real-time information. This study aims to implement the Fuzzy Logic Tsukamoto method in an Internet of Things (IoT)-based dam water level measurement system using the ESP8266. The research method employed is a descriptive method, which includes system design, water level sensor data collection, data processing using the fuzzy method, and system testing. In this study, the fuzzy input variable is the water level with linguistic sets of low, medium, and high, while the output variable is the dam status with the sets of safe, alert, and danger. Based on the test results, at a water level value of 40 cm, the membership degrees obtained were μ_low = 0.3, μ_medium = 1.00, and μ_high = 0.22. The fuzzy inference process produced a crisp output value using the Tsukamoto defuzzification method of 87.45, which is categorized as an alert condition. The test results indicate that the system is capable of processing sensor data accurately and providing real-time information on water level conditions through the internet network. Therefore, the implementation of Fuzzy Logic Tsukamoto in an IoT-based system using ESP8266 can be an effective and reliable solution for monitoring dam water levels and supporting fast and accurate decision-making.